Reaktualisasi Nilai-Nilai Tasawuf Akhlāqi pada Pola Hubungan Pendidik dengan Peserta Didik dalam Pendidikan Islam - Rahman, Rahman (Institut Agama Islam Negeri (IAIN) Bone, 2019)
This paper examines the reactualization of the doctrinal values of Sufism andthe learners in Islamic education. This research is a library by using qualitativedescriptive analysis. Data instruments are related reference searches in thelibrary as well as reviewing books relevant to the discussion. From this paper, itis known that the pattern of interaction between educators and students must bebased on the relationship of sincerity, friendship relations, protection relations,the relationship of transparency, and the relationship of mutual understanding.From these patterns give birth to the attitudes that must be presented byeducators, such as sincere in delivering knowledge, gentle, thoughtful, just donot choose love, open and appreciate the opinions of learners. Similarly, learnersare required to have sincere attitudes to receive lessons from their students,obey, obey, be patient, have a willingness or strong ideals, and are notdiscouraged and fervent in seeking knowledge, courtesy, and respect forteachers. The main task of learners is learning. The pattern of interaction basedon the values of Sufism of Akhlāqi needs to be rebuilt in order to create aharmonious relationship pattern, so that educational objectives can be achieved.In order to foster a good student relationship to educators, ethical values becomevery important to be the foundation, because with the etilose human beings havevalue and degrees. The relationship of educators with learners is close, whichapplies on the basis of mutual giving and receiving, but the closeness is also notborderless proximity, ignoring ethical values and politeness in social relations,so that Could make the loss of the educator's dignity in front of the students andthe students ' respect for educators. The pattern of the relationship in question isharmonious and ethical value of Humanitis.